1976
DOI: 10.1080/00039896.1976.10667193
|View full text |Cite
|
Sign up to set email alerts
|

Initial Occupational Exposure to Lead

Abstract: Serial chromosome and biochemical studies were carried out in 11 subjects before and during initial occupational exposure to moderate quantities of lead fumes in a storage battery plant. The rate of abnormal metaphases, mostly with chromatid and one-break chromosome aberrations, was approximately doubled after one month of work; it further increased after two months of work; remained in this range up to seven months of exposure; and then tended to decrease somewhat. Blood lead levels increased progressively in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…Exposure to lead in this study did not affect mitotic activity, as both groups had similar NDI (NDI exp =2.17 vs NDI cont= 2.13), which is in line with the report by Palus et al (41). Minozzo et al (58), in contrast, found significantly higher NDI in battery recycling workers than controls and other studies (99)(100)(101) showed increased mitotic activity in lead exposure.…”
Section: Resultssupporting
confidence: 91%
“…Exposure to lead in this study did not affect mitotic activity, as both groups had similar NDI (NDI exp =2.17 vs NDI cont= 2.13), which is in line with the report by Palus et al (41). Minozzo et al (58), in contrast, found significantly higher NDI in battery recycling workers than controls and other studies (99)(100)(101) showed increased mitotic activity in lead exposure.…”
Section: Resultssupporting
confidence: 91%
“…This assumption is also compatible with various kinds of earlier data on the elimination (1,(11)(12)(13)(14)20,(27)(28)(29)36,37,40,46,50,53,54,56,65), if a second , slow compartment is taken into consideration, and on the accumulation (5,24,27,28,37,38,48,65,67) of PbB.…”
Section: Discussionsupporting
confidence: 73%
“…Lead is excreted by the adult at a rate of approximately 30 lg/day by the kidney (Kehoe 1969). With increasing body stores, this may rise considerably but is rarely more than 20 mg/day (Chisolm et al 1975;Forni et al 1976). Excretion may be due both to glomerular filtration and in part to shedding of tubular epithelial cells where the lead tends to concentrate (Bennett 1985).…”
Section: Introductionmentioning
confidence: 98%